Persistent or recurrent Castleman′s disease - Look out for a lurking lymphoma! - Shalinee Rao; Anita Ramesh; Aarthi Rajkumar; Rekha Arcot; Sarah Kuruvilla (Indian Journal of Medical and Paediatric Oncology)
Castleman′s disease, a rare condition of uncertain etiology clinically presents in isolated form or as a multicentric disease. The multicentric form can develop malignancies such as Kaposi′s sarcoma or lymphomas. We present a case of Castleman′s disease with coexisting interfollicular Hodgkin′s lymphoma that was confirmed by immunohistochemistry. This case report highlights the fact that an occult lymphoma has to be ruled out in persistent or recurrent Castleman′s disease.